Psychology for physical educators student in focus - Liukkonen, Jarmo; Auweele,Yves Vanden; Vereijken, Beatrix; Alfermann, Dorothee; Theodorakis, Yannis (Human Kinetics, 2007)
This new edition features practical examples with teacher applications & new textbook elements designed to make learning easier. The textbook is divided into four sections - promotion of lifelong health & fitness, promotion of social skills for life, promotion of self-concept & cognitive skills, & promotion of motor skills for life